2011
DOI: 10.3390/sym3020220
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Enantioselective Henry Reactions

Abstract: A large number of interesting organocatalytic enantioselective protocols have been explored and successfully applied in the last decade. Among them, the Henry (nitroaldol) reaction represents a powerful carbon-carbon bond-forming procedure for the preparation of valuable synthetic intermediates, such as enantioenriched nitro alcohols, which can be further transformed in a number of important nitrogen and oxygen-containing compounds. This area of research is still in expansion and a more complex version of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(42 citation statements)
references
References 75 publications
(60 reference statements)
0
41
0
1
Order By: Relevance
“…The most common approach to compounds 1 is represented by the enantioselective Henry (nitroaldol) reaction between aldehydes and nitromethane, which is catalysed by metal complexes or organocatalysts [1,[6][7][8][9][10][11][12][13][14][15][16].…”
Section: Scheme 1 Synthesis Of β-Amminoalcohols 2 Through β-Nitroalcmentioning
confidence: 99%
“…The most common approach to compounds 1 is represented by the enantioselective Henry (nitroaldol) reaction between aldehydes and nitromethane, which is catalysed by metal complexes or organocatalysts [1,[6][7][8][9][10][11][12][13][14][15][16].…”
Section: Scheme 1 Synthesis Of β-Amminoalcohols 2 Through β-Nitroalcmentioning
confidence: 99%
“…[9][10][11] With the optimized solvents in hand, the effect of temperature on enantioselectivity in the Henry reaction is also studied in a mixed protic solvent (EtOH/H 2 O, 3:1, v/v). The results from the different temperatures (Table 1) showed the enantioselectivity can not be further improved by lowering the temperature at the accompanying expense of increasing the reaction time.…”
Section: Synthesis Of No-type Inherently Chiral Calixmentioning
confidence: 99%
“…The resulting nitro alcohol (nitroaldol) products can be transformed into a number of nitrogen and oxygen-containing derivatives such as 1,2-amino alcohols, amino sugars, nitro ketones, nitro alkenes, ketones, and other important compounds. [9][10][11][12][13][14] It was reported that chiral N,O-type cupreidine derivatives can perform outstanding catalytical activities for Henry reaction. Mechanistic studies on their catalytic behaviors indicated they serve as acid-base bifunctional organocatalysts through H-bond interactions with the acceptor and donor components of the reactions through the quinuclidine nitrogen and the aromatic hydroxyl, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In both strategies, ketones, as less explored substrates in organocatalytic Henry reaction [103], were used allowing the achievement of the required chiral quaternary centers with excellent enantioselectivities.…”
Section: Xii4 Cinchona Alkaloids In Total Synthesismentioning
confidence: 99%